Shifts in the functional topography of frontal cortex-striatum connectivity in alcohol use disorder - Gerchen, Martin Fungisai; Kirsch, Martina; Kiefer, Falk; Kirsch, Peter (Addiction biology, 2019)
Frontostriatal circuits are centrally involved in the selection of behavioral programs and play a prominent role in alcohol use disorder (AUD) as well as other mental disorders. However, how frontal regions change their striatal connectivity to implement adaptive cognitive control is still not fully understood. Here, we developed an approach for functional magnetic resonance imaging (fMRI) connectivity analysis in which we change the focus from connectivity to individual voxels towards spatial information about the location of strongest functional connectivity. In resting state data of n = 66 participants with AUD and n = 40 healthy controls (HC) we used the approach to estimate frontostriatal connectivity gradients consistent with nonhuman primate tract-tracing studies, characterized for each frontal voxel the striatal peak connectivity location on this gradient (PeaCoG), and tested for group differences and associations with clinical variables. We identified a cluster in the right orbitofrontal cortex (rOFC) with a peak connectivity shift towards ventral striatal regions in AUD. Reduced variability of rOFC striatal peak connectivity in the AUD group suggests a “clamping” to the ventral striatum as the underlying effect. Within the AUD group striatal peak connectivity in the superior frontal gyrus was associated with self-efficacy to abstain from alcohol, in the medial frontal and dorsolateral prefrontal cortex with alcohol dependency, and in the right inferior frontal gyrus with the urge to consume alcohol. Our results demonstrate that the functional topography of frontostriatal circuits exhibits interindividual variability, which provides insight into frontostriatal network adaptations in AUD and potentially other mental disorders.
Online verfügbar: 23 November 2018
Gesehen am 28.03.2019